2020
DOI: 10.25122/jml-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Lipoic Acid as a Means of Influence on Systemic Inflammation in Type 2 Diabetes Mellitus Patients with Prior Myocardial Infarction

Abstract: Patients with combined coronary heart disease and diabetes mellitus make up a growing segment of the population and require a com¬prehensive treatment approach. Patients with concurrent diabetes mellitus and coronary heart disease have a worse projection. Under these conditions, the incidence of recurrent myocardial infarction, early disability due to complications, and the risk of coronary death are increased. Therefore, the priority task is to find ways to optimize drug treatment of this category of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…ALA has other beneficial effects such as vasorelaxation, a positive metabolic profile as well as an anti-inflammatory potential. 12 Additionally, according to the previous study, pretreatment of diabetic rats with ALA reestablished the infarct size-limiting effect of Post via regulating autophagy and improving mitochondrial function. 28 Therefore, it is inferred that the reduction of cardiac fibrosis can be attributed to both the recovery of cardiac autophagy and mitochondrial function, which improves the function of the heart.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…ALA has other beneficial effects such as vasorelaxation, a positive metabolic profile as well as an anti-inflammatory potential. 12 Additionally, according to the previous study, pretreatment of diabetic rats with ALA reestablished the infarct size-limiting effect of Post via regulating autophagy and improving mitochondrial function. 28 Therefore, it is inferred that the reduction of cardiac fibrosis can be attributed to both the recovery of cardiac autophagy and mitochondrial function, which improves the function of the heart.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, this compound is effective in I/R hearts in different ways including vasorelaxation, positive metabolic profile, and anti-apoptotic and antiinflammatory features. 12 It has been shown that ALA has also positive effects on the prevention and treatment of diabetes, 13 and preserves the heart from diabetic cardiomyopathy. 14 It seems that ALA can be more effective when it is used with another intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention with HPD + ALA + MFM significantly increases the SOD, CAT and GSH levels in diabetic rats, which were significantly decreased in diabetic rats fed with HFD + ALA + MFM as well as in HCD + ALA + MFM respectively when compared to the diabetic rats fed with rat chaw, ALA and metformin. Alpha-lipoic acid (ALA) is thought to be the most successful antioxidant in clinical trials (Bobe et al, 2020;Altunina, Lizogub and Bondarchuk, 2020;Viana et al, 2022;Najafi et al, 2022;Al Mosawi, 2023). It is a natural compound with diverse biochemical functions, had been reported to acts as a metal chelator, regenerates endogenous antioxidants such as vitamins C and E, oxidizes glutathione within the cell (Maciejczyk et al, 2022), and is a modulator of the signalling transduction of several pathways (Capece et al, 2022;Capece et al, 2023).…”
Section: Ossai N R; Ojieh a E; Nwangwa E K; Nwogueze B Cmentioning
confidence: 99%
“…The study aimed to evaluate the impact of ALA supplementation on inflammatory markers. After a 4-month period, researchers observed that ALA supplementation was associated with a significant decrease in the levels of CRP, IL-6, and TNF-alpha when compared to the placebo group [ 33 ].…”
Section: Relevant Clinical Trials That Have Used Non-traditional Ther...mentioning
confidence: 99%